2020
DOI: 10.3390/biom10070970
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Fucoidan-Based Drug Delivery System by Using Hydrophilic Anticancer Polysaccharides to Simultaneously Deliver Hydrophobic Anticancer Drugs

Abstract: Fucoidan, a natural sulfated polysaccharide, which can activate the immune response and lessen adverse effects, is expected to be an adjuvant agent in combination with chemotherapy. Using natural hydrophilic anticancer polysaccharides to simultaneously encapsulate hydrophobic anticancer drugs is feasible, and a reduced side effect can be achieved to amplify the therapeutic efficacy. In this study, a novel type of fucoidan-PLGA nanocarrier (FPN-DTX) was developed for the encapsulation of the hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 57 publications
(63 reference statements)
1
17
0
Order By: Relevance
“…The cytotoxic effects of DTX-encapsulated fucoidan-polymeric micelles poly(lactic-co-glycolic acid) nanocarriers against triple-negative breast cancer cells were reported earlier in 2020 [ 73 ]. In that study, fucoidan was derived from Fucusvesicululos , and MDA-MB-231 cells were used.…”
Section: Nanoparticles With Fucoidansmentioning
confidence: 97%
See 1 more Smart Citation
“…The cytotoxic effects of DTX-encapsulated fucoidan-polymeric micelles poly(lactic-co-glycolic acid) nanocarriers against triple-negative breast cancer cells were reported earlier in 2020 [ 73 ]. In that study, fucoidan was derived from Fucusvesicululos , and MDA-MB-231 cells were used.…”
Section: Nanoparticles With Fucoidansmentioning
confidence: 97%
“…In that study, fucoidan was derived from Fucusvesicululos , and MDA-MB-231 cells were used. The authors concluded that the nanoparticles effectively exerted better anti-cancer effects and were recognized as a competent drug delivery system [ 73 ]. Moreover, other investigators showed the synergistic effects of DTX and fucoidan in multifunctional nanoparticles encapsulated in green tea polyphenol and low-dose DTX within fucoidan-based nanoparticles against prostate cancer [ 74 ].…”
Section: Nanoparticles With Fucoidansmentioning
confidence: 99%
“…Seaweed polysaccharides have gained interest in this topic due to the already available know-how as they are easy to obtain and purify, cost effective, nontoxic, biodegradable, biocompatible, and easy to work with [172,230] . Also, using natural hydrophilic seaweed polysaccharides to encapsulate hydrophobic anti-cancer agents is practicable, and can diminish side effects and the dispersion of the chemotherapy agents in the human body, thus amplifying the therapeutic efficiency and efficacy [232] .…”
Section: Drug Delivery Systemmentioning
confidence: 99%
“…Results demonstrated that the curcumin associated to a carrageenan drug delivery was more active against the cancer cells than curcumin in its free form [230] . Similarly, Lai et al [232] used hybrid fucoidan -Poly(lactic-co-glycolic acid) to encapsulate a hydrophobic anti-cancer compound (docetaxel).…”
Section: Drug Delivery Systemmentioning
confidence: 99%
“…Four cancer-related research articles by Wang Q. et al [ 1 ], Miao Y. et al [ 2 ], Martínez-García D. et al [ 3 ], Thangaraj K. et al [ 4 ], and Lai Y. et al [ 5 ] demonstrate that several natural-based compounds/proteins could effectively influence the cancer formation and progression. These study findings unveil the relationship of the SUMO pathway and DAPK1 protein degradation, demonstrate the target modifications of novel protease could effectively and efficiently alter its anticancer bioactivity, study the survivin levels through potent STAT3 Inhibition in lung cancer, investigate the cell cycle arrest and mitochondria-mediated intrinsic apoptosis in colorectal carcinoma, and develop a Fucoidan-based drug delivery system by using hydrophilic anticancer polysaccharides to simultaneously deliver hydrophobic anticancer drugs, respectively.…”
mentioning
confidence: 99%